PFKFB3 activates CAD to enhance de novo pyrimidine synthesis for cell growth - Qingen Da; Yongfeng Cai; Qian Ma; Qiuhua Yang; Yapeng Cao; Yaqi Zhou; Dingwei Zhao; Zhiping Liu; Jiean Xu; Junming Quan; Liang Zhang; Rui Wang; et al. (Cell Reports)
Summary: Aerobic glycolysis, termed the Warburg effect, is one of the aberrant metabolic pathways in highly proliferating cells. Glycolysis provides glycolytic metabolites to support the generation of biomass, such as nucleotides, amino acids, and lipids. Research on the direct interactions between glycolysis and other metabolic pathways is an emerging field that has garnered significant interest. Phosphofructokinase-2/fructose-2,6-bisphosphatase 3 (PFKFB3) activates glycolysis by synthesizing fructose-2,6-bisphosphate (F2,6BP), which allosterically activates the rate-limiting enzyme 6-phosphofructo-1-kinase (PFK-1). In this study, we found that PFKFB3 directly interacts with and regulates the phosphorylation of carbamoyl-phosphate synthetase 2, aspartate transcarbamylase, and dihydroorotase (CAD), the enzyme catalyzing the first three steps of de novo pyrimidine synthesis. PFKFB3 inactivation reduced de novo pyrimidine synthesis, RNA and DNA production, and cell proliferation. Thus, the glycolytic activator PFKFB3 bridges glycolysis with pyrimidine synthesis, unites both glucose metabolism and nucleic acid metabolism, and contributes to cell proliferation under pathological conditions.